(untitled) (Global Journal of Science Frontier Research, 2012)
In this article, we discuss certain class of generalized functions for sine and cosine transforms. we, also obtain a new relationship between Fourier sine transform (Fourier cosine transform) and wavelet transform. Other related theorems are also established in concern.